2015
DOI: 10.1038/onc.2015.378
|View full text |Cite
|
Sign up to set email alerts
|

Sp100A is a tumor suppressor that activates p53-dependent transcription and counteracts E1A/E1B-55K-mediated transformation

Abstract: Human adenoviruses (HAdV) are used as a model system to investigate tumorigenic processes in mammalian cells where the viral oncoproteins E1A and E1B-55K are absolutely required for oncogenic transformation, because they simultaneously accelerate cell cycle progression and inhibit tumor suppressor proteins such as p53, although the underlying mechanism is still not understood in detail. In our present study, we provide evidence that E1B-55K binding to the PML-NB component Sp100A apparently has an essential rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Second, the PML‐NB component Sp100A does not activate p53 transcriptional activity upon binding to E1B. This effect is enhanced by E1B‐induced SUMOylation of Sp100A resulting in its relocalization into the nuclear insoluble matrix or into cytoplasmic inclusion bodies . Phosphorylation‐ deficient mutants of E1B showed that the transactivation activity of p53 is only partially inhibited although binding to p53 is comparable to WT E1B .…”
Section: Role Of E1b 55k In Cell Transformationmentioning
confidence: 99%
“…Second, the PML‐NB component Sp100A does not activate p53 transcriptional activity upon binding to E1B. This effect is enhanced by E1B‐induced SUMOylation of Sp100A resulting in its relocalization into the nuclear insoluble matrix or into cytoplasmic inclusion bodies . Phosphorylation‐ deficient mutants of E1B showed that the transactivation activity of p53 is only partially inhibited although binding to p53 is comparable to WT E1B .…”
Section: Role Of E1b 55k In Cell Transformationmentioning
confidence: 99%
“…Ubc9 represents the main SUMO-conjugating enzyme also involved in Sp100 SUMOylation (51). Thus, the inability of the E2A SCM to interact with Ubc9 might prevent an HAdV-mediated decrease in Sp100A SUMO moieties and thus block the transcription-activating properties (93). The loss of Sp100A protein levels and faulty PML track/RC cooperation in E2A SCM infection might in sum prevent the virus from exploiting beneficial Sp100A capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence demonstrates that the host cell broadly restricts chromatinization of the incoming viral genome during the earliest stages of infection. It is proposed that this restriction occurs via PML-associated proteins Daxx, ATRX, and Sp100 [144][145][146] as well as the chromatin regulator SPOC1 [147]. Outside of viral infection, the Daxx/ATRX histone chaperone complex is thought to promote chromatin silencing via deposition of the H3.3 histone variant.…”
Section: Impact Of E4orf3 On Host Chromatin and Chromatinization Of Vmentioning
confidence: 99%